3D posture reconstruction and human animation from 2D feature points - Zhao, J.; Li, L.; Keong, K. (Computer Graphics Forum, 2005)
An optimal approach is proposed in this paper for posture reconstruction and human animation from 2D feature points extracted from the monocular images containing human motions. Biomechanical constraints are encoded in every joint of the adopted 3D skeletal human model to make sure that each state of the joints represents a physically valid posture. Size of the human model is adjusted to be consistent with the human figure represented by feature points. Energy Function is defined to represent the residuals between the extracted 2D feature points and the corresponding features resulted from projection of the 3D human model. Local Adjustment and Global Adjustment procedures are proposed to place the joints and body segments into proper locations and orientations in 3D space to create the posture with the minimum value of Energy Function. To find the optimal solution of the ill-posed recovery problem from 2D to 3D, Genetic Algorithm is employed in the high-dimensional parameter space by considering all the parameters simultaneously. Smooth and continuous changes between consecutive frames are considered in development of the human animation procedure. The proposed approach produces optimal reconstruction results of any possible human postures and movements. It is different from classical kinematics and dynamics formulations, and is an attempt to bridge the gap between computer vision and computer animation in human motion study.